2020
DOI: 10.3390/v12040424
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage ZCSE2 is a Potent Antimicrobial against Salmonella enterica Serovars: Ultrastructure, Genomics and Efficacy

Abstract: Developing novel antimicrobials capable of controlling multidrug-resistant bacterial pathogens is essential to restrict the use of antibiotics. Bacteriophages (phages) constitute a major resource that can be harnessed as an alternative to traditional antimicrobial therapies. Phage ZCSE2 was isolated among several others from raw sewage but was distinguished by broad-spectrum activity against Salmonella serovars considered pathogenic to humans and animals. Lytic profiles of ZCSE2 against a panel of Salmonella w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Interestingly, the C-terminus of the tail fiber of the Loughboroughvirus phages (S144, SE4 and ZCSE2) is more similar to the otherwise unrelated Cronobacter phages GAP31 and GAP32 [71,72] than to the Rosemountvirus phages. While phages SE4 and ZCSE2 have been proven to infect many different Salmonella serovars, no bacterial strains from other genera were tested [35,43]. Given the similarity to phage S144 including the C-terminus of the tail fiber, involved in the host recognition and binding, we suggest that also phages SE4 and ZCSE2 may infect C. sakazakii and may thus be polyvalent phages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the C-terminus of the tail fiber of the Loughboroughvirus phages (S144, SE4 and ZCSE2) is more similar to the otherwise unrelated Cronobacter phages GAP31 and GAP32 [71,72] than to the Rosemountvirus phages. While phages SE4 and ZCSE2 have been proven to infect many different Salmonella serovars, no bacterial strains from other genera were tested [35,43]. Given the similarity to phage S144 including the C-terminus of the tail fiber, involved in the host recognition and binding, we suggest that also phages SE4 and ZCSE2 may infect C. sakazakii and may thus be polyvalent phages.…”
Section: Discussionmentioning
confidence: 99%
“…Taxonomically, phage S144 can be classified as a member of the recently approved Loughboroughvirus genus, containing only two other members: the Salmonella phages ZCSE2 [43] and SE4 [35]. Since these phages are highly similar to the members of the Rosemountvirus genus, we proposed a new subfamily, the 'Salusvirinae'.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many papers have been published recently which described bacteriophages that might be used in phage therapy against Salmonella . They include reports on characterization of previously unknown bacteriophages having the potential for use in phage therapy [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], experimental studies with bacteriophages applied to poultry [ 21 , 22 , 23 , 24 , 25 , 26 ], and the use of bacteriophages in experimental phage therapy in mouse [ 27 , 28 , 29 , 30 ] or pig [ 31 ] models. Although promising results were obtained in these studies, and economic analyses have been performed to assess costs and benefits of the use of phage therapy for the control of Salmonella in poultry [ 9 , 32 ], it is evident that the host range of the vast majority of Salmonella phages is restricted to specific strains or serovars.…”
Section: Introductionmentioning
confidence: 99%
“…The proposal of the use of phage therapy to treat Salmonella infections has been published previously in many reports. Those studies led to determination of properties of various Salmonella -specific phages [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], effects of application of phages to poultry [ 22 , 23 , 24 , 25 , 26 , 27 ], and results of experimental use of phages in therapies of infected animals [ 28 , 29 , 30 , 31 , 32 ]. In addition, economic analyses of potential use of anti- Salmonella phage therapy in poultry have also been published [ 1 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, economic analyses of potential use of anti- Salmonella phage therapy in poultry have also been published [ 1 , 33 ]. Despite promising results of these studies, it was also indicated that most phages infecting S. enterica have a relatively narrow host range, specific to one or a few serovars or strains [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 34 ]. Thus, characterization of newly isolated bacteriophages infecting this bacterium is reasonable.…”
Section: Introductionmentioning
confidence: 99%